2019
DOI: 10.1371/journal.pone.0216585
|View full text |Cite|
|
Sign up to set email alerts
|

Imagine All The Synchrony: The effects of actual and imagined synchronous walking on attitudes towards marginalised groups

Abstract: Stereotyping is a pervasive societal problem that impacts not only minority groups but subserves individuals who perpetuate stereotypes, leading to greater distance between groups. Social contact interventions have been shown to reduce prejudice and stereotyping, but optimal contact conditions between groups are often out of reach in day to day life. Therefore, we investigated the effects of a synchronous walking intervention, a non-verbal embodied approach to intergroup contact that may reduce the need for op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 67 publications
(72 reference statements)
1
26
0
Order By: Relevance
“…These findings show that increases in empathy and positive attitudes only occurred after participants imagined coordinating with out-group but not in-group members. The findings reported here therefore replicate those of Atherton et al (2019) in a new context, showing that imagined coordination can be utilized to foster better attitudes towards members of disenfranchised groups. Furthermore, they highlight that this effect is modulated by group membership, further supporting the idea that coordination doesn't unilaterally increase pro-social behaviours, but differentially changes perceptions of in-group and out-group members.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…These findings show that increases in empathy and positive attitudes only occurred after participants imagined coordinating with out-group but not in-group members. The findings reported here therefore replicate those of Atherton et al (2019) in a new context, showing that imagined coordination can be utilized to foster better attitudes towards members of disenfranchised groups. Furthermore, they highlight that this effect is modulated by group membership, further supporting the idea that coordination doesn't unilaterally increase pro-social behaviours, but differentially changes perceptions of in-group and out-group members.…”
Section: Discussionsupporting
confidence: 76%
“…Similarly, imagining being in a crowd reduces people's helping behaviour on a subsequent task, in line with the bystander effect (Garcia, Weaver, Moskowitz, & Darley, 2002). Previous work has also shown that not only are people able to successfully perform imagined coordinated actions (Vesper, Knoblich, & Sebanz, 2014), but that doing so leads to similar increases in pro-social attitudes that are shown to follow actual coordination (Cross et al, 2017;Atherton et al, 2019). Some speculate that coordination may have long been used as a tool to foster a common group mentality amongst co-actors (McNeil, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…expectation/ demand effects; and effects of having viewed different videos across conditions of people walking either in synchrony or asynchrony; Atherton et al, 2019;Stupacher et al, 2017). To isolate expectations from any effect of first-person mental simulation, we asked participants to make predictions about other people, not themselves; we avoided including images, videos, or unnecessary details that could prompt vivid imagery; we kept vignettes brief; and we did not ask participants to spend additional time elaborating on vivid mental imagery after reading (as done in Atherton et al, 2019).…”
Section: Do Participants Have a Priori Expectations About Synchrony Amentioning
confidence: 99%